SOSIALISASI PENGGUNAAN LITERASI DIGITAL PADA MASYARAKAT DALAM PEKERJAAN PEMELIHARAAN KONSTRUKSI JALAN SERTA BANGUNAN PELENGKAP - Made Novia Indriani; Ida Bagus Wirahaji; Ida Ayu Putu Sri Mahapatni; A.A.A Made Cahaya Wardani (JURNAL SEWAKA BHAKTI, 2022)
This community service aims to further enrich insight into the condition of road pavement construction and complementary buildings (road drainage and culverts) on environmental roads in Sibanggede Traditional Village, Abiansemal District, Badung Regency. non-governmental activities in maintaining the condition of road pavement construction as access in carrying out various activities, through the activity "Socialization of the Use of Digital Literacy in the Community in Maintenance Works of Road Construction and Complementary Buildings". Data was collected using the methods of interview, observation, and documentation. The stages of service activities include: initial survey and data inventory, location measurement, calculation of RAB and design drawings, video content creation activities related to community service activities for the use of digital literacy in road construction maintenance work and complementary buildings.